Comparison of 3 T mpMRI and pelvic CT examinations for detection of lymph node metastases in patients with prostate cancer. Issue 147 (February 2022) - Valentin, B.; Arsov, C.; Ullrich, T.; Demetrescu, D.; Morawitz, J.; Al-Monajjed, R.; Quentin, M.; Kirchner, J.; Esposito, I.; Albers, P.; Antoch, G.; Schimmöller, L.
Highlights: MRI provides a moderate risk assessment for LNM detection. LNM up to 4 mm could be detected with MRI. CT was limited in detecting LNM. Abstract: Purpose: This study investigates preoperative lymph node metastases (LNM) detection accuracy by MRI and CT in patients with prostate cancer (PCA). Methods: All patients with preoperative MRI, CT or both and subsequent radical prostatectomy (RPE) and lymphadenectomy (LA) were included in this retrospective cohort study. Prostate specific antigen (PSA), PI-RADS, ISUP grade group, clinical and pathological tumor (T) stage was compared between negative and positive nodal (N) stage. LNM were assessed with size and localization and weather they were preoperatively detected or not. In patients with preoperative CT and MRI, the results were compared intermodally. The reference standard was the histopathological results after RPE and LA. Results: A total of 228 patients were analysed including 24 patients with confirmed LNM (N1; 11%). PSA (median 9.7 vs. 14 ng/ml), PI-RADS (median 4 vs. 5), ISUP (median 2 vs. 4), and cT/pT-stage (median T2 vs. T3) was significantly higher in patients with LNM. No LNM were found in patients with ISUP-1-PCA. MRI was able to detect 67% of patients with LNM. Lymph node metastases presented on MRI predominantly small, round-shaped, located parailiacally with a minimum SAD of 4 mm (vs. CT SAD of 8 mm). In comparison, MRI was superior to CT in the detection of LNM (sensitivity 81% vs. 33%; specificity 99% vs. 97). Conclusion: LNM were very rare in patients with PSA < 10 ng/ml, PI-RADS ≤ 4, and ≤ cT2. MRI could detect LNM up to 4 mm with a moderate sensitivity and high specificity. Thus, MRI might optimise the preoperative diagnostic and therapy planning of patients with PCA, whereas CT was clearly limited for N-stage assessment.